PENGARUH KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA FUTSAL ADIDAS DI WILAYAH JAKARTA TIMUR - Saidani, Basrah; Rachman, M. Aulia; Rizan, Mohammad (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
The purposes of this research are to describe about product quality, product design and purchasing decision and test the product quality and product design variables that influence the purchasing decision of Adidas’ futsal shoes. This research used descriptive and explanatory methods. The unit analysist of this research are the consumers of Adidas at East of Jakarta. Total sample of this research are 100 respondences while the analysis tools that are used in this research are SPSS 18.0. The result of this research shows: (1) product quality is significantly influencing the purchasing decision by 10.7%; (2) product design is significantly influencing the purchasing decision by 7,5%; (3) simultaneously product quality and product design are significantly influencing the purchasing decision by 17.6%. The remaining 82,4% is influenced or explained by other variables that are not included in this research. Keywords: product quality, product design, purchasing decision and Adidas’ futsal shoes.